一种新型端粒酶触发DNA纳米机器及其构建方法 (2022)
本发明公开了一种端粒酶触发DNA纳米机器及其构建方法，其包括金纳米粒子、探针机械臂序列S1、端粒酶引物序列S2、ATP适体序列S3、反义DNA序列S4，探针机械臂序列S1 5'端的巯基连接在金纳米粒子上，探针机械臂序列S1靠近3'端的部分序列形成环状结构，端粒酶引物序列S2与探针机械臂序列S1互补杂交形成茎-环结构，ATP适体序列S3 3'端的巯基连接在金纳米粒子上，反义DNA序列S4与ATP适体序列S3互补杂交，所述反义DNA序列S4的3'端修饰光敏剂，所述ATP适体序列S3 5'端修饰双模式成像基团。以肿瘤细胞内的端粒酶触发DNA纳米机器，高丰度的ATP作为驱动，释放反义DNA及光敏剂，实现肿瘤细胞基因治疗、光动力治疗联合治疗、端粒酶的检测及肿瘤细胞的双模式成像。 The invention discloses a telomerase-triggered DNA nano machine and a construction method thereof, which comprises gold nanoparticles, a probe mechanical arm sequence S1, a telomerase primer sequence S2, an ATP aptamer sequence S3 and an antisense DNA sequence S4, the sulfydryl at the 5' end of the probe mechanical arm sequence S1 is connected to the gold nanoparticles, a part of the sequence, close to the 3' end, of the probe mechanical arm sequence S1 forms an annular structure, the telomerase primer sequence S2 and the probe mechanical arm sequence S1 are complementarily hybridized to form a stem-loop structure, the sulfydryl at the 3' end of the ATP aptamer sequence S3 is